A low-cost electrochemical biosensor platform for C-reactive protein detection (2021)
Antibiotic resistance is a worldwide problem aggravated by the overuse of prophylactic antibiotic therapies and lack of real-time biosensing equipment to differentiate viral from bacterial infections at the Point of Care (POC), particularly in rural areas with limited access to clinical laboratory facilities. As recent studies reveal the potential of C-Reactive Protein (CRP) and other acute phase biomarkers to achieve early determination of etiology in acute febrile illness, novel biosensing equipment become a plausible approach in preventing the unnecessary prescription of antibiotics. A low-cost experimental platform was engineered to measure CRP concentrations in 50 μL samples of buffer and enriched plasma, using label-free antigenic probes, legacy electrochemical methods and open-source hardware. The prototype presents a portable, cost-effective device for use at the POC with a simplified user interface that can be used wirelessly by healthcare professionals using a mobile phone or laptop. Based on the measured CRP levels, the device suggests if the acute febrile episode is likely to be of bacterial etiology.